Sleep status and its association with dietary habits among children and adolescents in Shandong Province, China: a cross-sectional study - Zhihao Huang; Chen Tong; Rumeng Cheng; Kunzong Tian; Yuting Jiang (BMC Public Health)
Abstract Background Insufficient sleep is a widespread issue among children and adolescents, influenced by various factors, including dietary habits. This study aimed to examine the relationship between dietary habits and sleep insufficiency in children and adolescents aged 6 to 18 in Shandong Province, China. Methods Data were derived from a 2024 survey assessing sleep status among children and adolescents in Shandong Province. the prevalence of insufficient sleep was determined, and univariable Χ² test was used to explore associations between daily life behaviors and sleep duration. Multivariable logistic regression was employed to analyze the effect of specific dietary habits on sleep insufficiency, adjusting for potential confounding factors. Results The overall prevalence of insufficient sleep was 53.28%. After adjusting for confounders, the logistic regression model indicated that regular breakfast consumption 4 ~ 6 times per week (OR = 0.578, 95% CI 0.522 ~ 0.640) or every day (OR = 0.502, 95% CI: 0.450 ~ 0.561) was associated with significantly lower odds of insufficient sleep. Higher vegetable intake more than five times per week (OR = 0.376, 95% CI: 0.338 ~ 0.418) and fruit consumption 4 ~ 5 times per week (OR = 0.866, 95% CI: 0.816 ~ 0.918) or more than five times per week (OR = 0.446, 95% CI: 0.405 ~ 0.490) were also linked to reduced odds of insufficient sleep. Conversely, higher sugary beverage consumption 4 ~ 5 times per week (OR = 2.066, 95% CI: 1.903 ~ 2.243) or more than five times per week (OR = 2.021, 95% CI: 1.838 ~ 2.223) significantly increased the likelihood of insufficient sleep. Fast food consumption 2 ~ 3 times per week (OR = 1.025, 95% CI: 1.003 ~ 1.048) or more than three times per week (OR = 1.036, 95% CI: 1.002 ~ 1.071) was also associated with higher odds of insufficient sleep (P < 0.05). Conclusion Dietary habits significantly influence sleep duration among children and adolescents in Shandong Province. Regular breakfast consumption, increased intake of vegetable and fruit, and reduced consumption of sugary beverage and fast food were associated with improved sleep duration. These findings underscored the importance of promoting healthy eating behaviors as a key strategy for addressing sleep-related issues and improving overall well-being in young populations.